TEORI ELABORASI SEBAGAI BAGIAN DARI SUATU STRATEGI PEMBELAJARAN - Sujarwo, Sujarwo (MAJALAH ILMIAH PEMBELAJARAN, 2009)
The theory of prescriptive learning am theories and principles pembelajaran that place the condition and learning results as means increasing attention (retention) participants of student against an object of the analysis (the contents of the study field). So that retention increases, then the educator must connect new knowledge with the cognitive structure that was owned. The theory of prescriptive learning suggest that retention increases, then learning begin by putting forward the framework of the contents learning, just afterwards in stages elaborate available parts in the framework of the contents, and permanently connect each elaboration stage in the framework of the contents. Efforts alternative the organising strategy of the contents learning could member the opportunity and facilitate the increase in studying results by applying principles of the elaboration model. The potential for this model apparently in the place arrangement of the contents that more stress the place from the public to rinsi and is accompanied by the existence pensintesis around several procedures that are included in the contents whole that is studied. By referring from theory of the cognitive structure and the process of participants’s memory of student, the potential elaboration model moved the formation of the cognitive structure just as the representation of studying results. The contents of the study field that is organised by following the guest plate of principles of the potential public can facilitate the working schemata that is had by participants the student in carrying out the process of the assimilation and accommodation. The theory of elaboration prescribes the organising method pembelajaran by following the place of the public to rins. The place of the public to rinsi is begun with put forward epitome (the structure of the contents of the study field that is studied) afterwards elaborate available parts in epitome in a specific manner